PREFERENSI MASYARAKAT TERHADAP LEMBAGA ZAKAT DAN BENTUK-BENTUK PEMBERDAYAAN DANA ZAKAT - Ahmad Mifdlol Muthohar (Inferensi Jurnal Penelitian Sosial Keagamaan, 2017)
This study aims to find out the attitude of muzaki in handing over the zakat fund and their perspective of the zakat institution. This study used a qualitative approach, located in 13 cities. The research findings showed that according to muzaki, paying zakat to zakat institution is more ideal, however, they prefer to pay it with two different ways; first is to zakat institution and second is directly given to those who deserve to receive it. Muzaki prefer to pay their zakat to private zakat institutions rather than to those belong to government. Then Zakat funds should be managed by the institution of zakat. If the government manages the zakat, it should be fair and believable. Furthermore, muzaki are more satisfied when zakat institutions distribute the zakat to people around muzaki. It is for the Benefit of the most desired purpose that is educational, social, religious, economic empowerment and health.